Radiopacity of Portland Cement Associated With Different Radiopacifying Agents - Hungaro Duarte, Marco Antonio; de Oliveira El Kadre, Guaniara D'arc; Vivan, Rodrigo Ricci; Guerreiro Tanomaru, Juliane Maria [UNESP]; Tanomaru Filho, Mario [UNESP]; de Moraes, Ivaldo Gomes (Elsevier B.V., 2009)
This study evaluated the radiopacity of Portland cement associated with the following radiopacifying agents: bismuth oxide, zinc oxide, lead oxide, bismuth subnitrate, bismuth carbonate, barium sulfate, iodoform, calcium tungstate, and zirconium oxide. A ratio of 20% radiopacifier and 80% white Portland cement by weight was used for analysis. Pure Portland cement and dentin served as controls. Cement/radiopacifier and dentin disc-shaped specimens were fabricated, and radiopacity testing was performed according to the ISO 6876/2001 standard for dental root sealing materials. Using Insight occlusal films, the specimens were radiographed near to a graduated aluminum stepwedge varying from 2 to 16 mm in thickness. The radiographs were digitized and radiopacity compared with the aluminum stepwedge using Digora software (Orion Corporation Soredex, Helsinki, Finland). The radiographic density data were converted into mmAl and analyzed statistically by analysis of variance and Tukey-Kramer test (alpha = 0.05). The radiopacity of pure Portland cement was significantly lower (p < 0.05) than that of dentin, whereas all cement/radiopacifier mixtures were significantly more radiopaque than dentin and Portland cement alone (p < 0.05). Portland cement/bismuth oxide and Portland cement/lead oxide presented the highest radiopacity values and differed significantly from the other materials (p < 0.05), whereas Portland cement/zinc oxide presented the lowest radiopacity values of all mixtures (p < 0.05). All tested substances presented higher radiopacity than that of dentin and may potentially be added to the Portland cement as radiopacifying agents. However, the possible interference of the radiopacifiers with the setting chemistry, biocompatibility, and physical properties of the Portland cement should be further investigated before any clinical recommendation can be done. (J Endod 2009,35:737-740)
Keywords: Portland cement; radiopacifying agents; radiopacity